2010
DOI: 10.1007/s00239-010-9349-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Lepidopteran Silk Proteins: Insights from the Ghost Moth, Hepialus californicus

Abstract: Silk production has independently evolved in numerous arthropod lineages, such as Lepidoptera, the moths and butterflies. Lepidopteran larvae (caterpillars) synthesize silk proteins in modified salivary glands and spin silk fibers into protective tunnels, escape lines, and pupation cocoons. Molecular sequence data for these proteins are necessary to determine critical features of their function and evolution. To this end, we constructed an expression library from the silk glands of the ghost moth, Hepialus cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…This family of natural protein fibres, which is widely produced by all spiders [1,2,3,4], many insects [2,5,6,7,8,9,10] and some other arthropods [2,11,12,13], has provided inspiration for artists [14], resources for traders [15,16,17] and motivation for scientists [18,19,20,21], from its earliest use for textiles in China [17], to the latest scientific research into advanced biomaterials and other uses [22,23,24,25,26,27]. Much of this endeavour has concentrated on the impressive mechanical properties of fibres produced by Lepidopteran larvae (i.e., the domesticated Bombyx mori ( B. mori ) and other wild silk moths) or spiders [4,21,28,29,30,31,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…This family of natural protein fibres, which is widely produced by all spiders [1,2,3,4], many insects [2,5,6,7,8,9,10] and some other arthropods [2,11,12,13], has provided inspiration for artists [14], resources for traders [15,16,17] and motivation for scientists [18,19,20,21], from its earliest use for textiles in China [17], to the latest scientific research into advanced biomaterials and other uses [22,23,24,25,26,27]. Much of this endeavour has concentrated on the impressive mechanical properties of fibres produced by Lepidopteran larvae (i.e., the domesticated Bombyx mori ( B. mori ) and other wild silk moths) or spiders [4,21,28,29,30,31,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…h‐fibroin is a large and highly repetitive gene whose product serves as a major component of silk fiber. Its nonrepetitive N‐terminal or C‐terminal sequence has been identified in several lepidopteran families such as Saturniidae, Bombycidae, Pyralidae, Yponomeutidae, and Hepialidae (Sezutsu & Yukuhiro, ; Fedič et al ., ; Yonemura & Sehnal, ; Sezutsu et al ., , b; Collin et al ., ; Sezutsu et al ., ; Suriana et al ., ). We found that the products of contig 27 (accession number LC001862) and contig 61 (LC001861) were homologous to the C‐termini and N‐termini of Bombyx H‐fibroin and other Saturniidae fibroins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One percent variation may result from polymorphism between diff erent strains (Zhou et al, 2000). Besides that, Collin et al (2010) was aligned H-fi broin of H.californicus and did not reveal any variation intra those population. The fi broin protein is tipycal structural protein, and the main protein in silk fi ber, that are spesies spesifi c (Zurovec & Sehnal 2002;Mondal et al, 2007).…”
Section: Conserved Nature Of First Exon Coding Regionmentioning
confidence: 85%
“…To date, all silk and fi broin gene studies of Lepidoptera have focused on B. mory (Bombycidae) (Zhou et al, 2000;Katsuhiko et al, 2007;Lefevre et al, 2007), Antheraea spesies and Samia cynthia ricini (Saturniidae) (Da a et al, 2001a, b;Sezutsu et al, 2009;Sezutsu & Yukuhiro, 2000;Sezutsu et al, 2010), Araneus diadematus, and Nephila edulis (Araneoidae), Galleria mellonella, and Hepialus californicus (Hepialidae) (Zurovec & Sehnal, 2002;Yonemura & Sehnal, 2006;Chen et al, 2006;Saravanan et al, 2006;Collin et al, 2010). No date for C. trifenestrata.…”
Section: Introductionmentioning
confidence: 99%